2018
DOI: 10.18203/issn.2454-5929.ijohns20183455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of otological and audiological outcome of type-I tympanoplasty using composite tragal perichondrium and temporalis fascia as graft

Abstract: <p class="abstract"><strong>Background:</strong> The most frequently used technique for the repair of TM perforation is underlay grafting of temporalis fascia in normally ventilated middle ears. In advanced middle ear pathology, large perforations, atelectatic drum or retraction pockets, temporalis facia may cause higher failure rates. In such cases, a more rigid grafting material such as cartilage is preferred because of its increased stability and resistance to middle ear pressure even in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…In comparison of Perichondrial graft uptake Nitin p et al [13] A comparative study conducted by Avani Jain et al [19] between island cartilage graft vs temporalis fascia graft in type 1 tympanoplasty showed a graft uptake rate of 97.1% for island cartilage graft which is close to our graft uptake rate of 100%.…”
Section: Type Of Cartilage Techniquesupporting
confidence: 76%
See 1 more Smart Citation
“…In comparison of Perichondrial graft uptake Nitin p et al [13] A comparative study conducted by Avani Jain et al [19] between island cartilage graft vs temporalis fascia graft in type 1 tympanoplasty showed a graft uptake rate of 97.1% for island cartilage graft which is close to our graft uptake rate of 100%.…”
Section: Type Of Cartilage Techniquesupporting
confidence: 76%
“…Our literature search has not revelaed a cartilage graft uptake of 100% in perichondrial graft as seen in the present study. In comparison of Temporalis fascia graft uptake with other studies Lackany et al [14] showed a graft uptake of 80%, Dabhorkar et al [18] 84%, Patil et al [17] 86.67% , Nitin p et al [13] 90% and Sprem N et al [15] 91% of successful temporalis fascia graft uptake which showed a lower value when compared to the present study where the graft uptake was 93.3%. On the contrary Harman and tang [20] showed 95.3% of temporalis fascia graft, Mathai et al [21] 95%, Singh et al [11] 95% which showed higher value when compared to the present study of 93.3% successful temporalis fascia graft uptake.…”
Section: Type Of Cartilage Techniquecontrasting
confidence: 48%
“…In a similar study by Sharma et al, the mean AB gap measured pre operatively in cartilage group was 36.38±6.10 dB which improved to 18.13±5.8 dB post operatively. 23 Fascia group showed improvement from 28.73±5.82 to 15.23±8.14. Results were statiscally highly significant and comparable in both cartilage and fascia group in terms of hearing gain after tympanoplasty.…”
Section: Discussionmentioning
confidence: 89%
“…The commonest presenting complaint was otorrhea (100%) followed by hearing loss (69.1%) 12.7% of patients had ringing sensation of the ear, 4.5% had vertigo and 5.4% had associated ear ache. In the study conducted by Sharma N et al 6 the commonest presenting complaint was ear discharge (100%) followed by hearing loss (95%), tinnitus (6.25%) and earache (3.75%), none had vertigo. Majority of the patients had a long standing disease with duration ranging from 3 months to 40 years.…”
Section: Discussionmentioning
confidence: 95%